Children's Talk in Communities & Classrooms - Vernon-Feagans, Lynne (University of North Carolina, 1996)
Almost all young children around the world come to formal schooling eager to learn even though this new educational milieu will challenge their intellectual, social, and emotional development. These children often come from a variety of cultural, ethnic, and economic backgrounds that create important differences among them at school entry. These differences have often been used as an excuse by educators for the poor performance of some of these children as they face the demands of school learning. This book traces the transition of a group of poor African-American children in semi-rural North Carolina, who, because of ethnicity and economic circumstances, were at risk for a poor transition to school. Half these children were part of an intensive early daycare intervention program to prepare them for formal schooling and half were not. Through an examination of talk and interviews within their home community and with teachers and peers in the classroom, a portrait is painted of the transition to school of these children and their families. Without purposeful malice from other children or teachers, the children became less successful and more marginalized in the classroom, creating a deceptively benign environment for their less optimal treatment there. This book aims to provide a better understanding of how the culture of the classroom may contribute to children's learning and perception about school, and suggests some helpful strategies for the successful engagement between classroom and child that might create more successful schooling for all children.